PENGARUH LEVERAGE, KOMPETISI, DAN PERTUMBUHAN PERUSAHAAN TERHADAP CARBON EMISSION DISCLOSURE (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN PERIODE 2015 – 2017) - Rachmad Hidayat Pranasyahputra; Trismayarni Elen; Kurnia Sari Dewi (Jurnal Akuntansi Trisakti, 2020)
This study aims to determine and analyze the effect of leverage, competition, and company growth on carbon emission disclosure. The research sample have used 32 companies with the period 2015-2017. The data used in this study is to use secondary data from the company's annual report that obtained from the BEI official website. The method used is a multiple regression technique that tests variables to determine the effects of factors that cause carbon emission disclosure. The results of this study indicate that there is a significant positive effect on the competition variable on carbon emission disclosure and no significant positive effect on the variable leverage and company growth on carbon emission disclosure.